Rate of profit, distribution and growth : two views - Kregel, J. A. (London, Macmillan, 1971)
This book attempts to integrate developments in capital theory and show their implications for models of long-run economic growth in mature capitalistic economies.
Includes bibliographical references and index.
oif 16/02/2019
Loans
Keywords: Profit--Mathematical models; Economic development--Mathematical models; Economics